PERENCANAAN PROGRAM BIDANG PENDIDIKAN DINAS PENDIDIKAN DAN KEBUDAYAAN DENGAN BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN SIAK TAHUN 2016 - Nasrul "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Educational planning as a process of preparing a set of alternative decisions for future activities that are directed towards achieving goals with optimal effort taking into account the facts that exist in the field of education as a whole. The program is a policy instrument that contains one or more activities carried out by government agencies / institutions to achieve goals and objectives and obtain budget allocations, or activities coordinated by government agencies. The purpose of this study was to describe the 2016 Siak District education program planning. This research method uses a qualitative approach with the type of descriptive research Based on the results of the study indicate that the planning of the related education program is the Department of Education and Culture in the field of elementary school development and the field of junior high school development with the Regional Development Planning Agency Head of Education and Inspectorateassupervision. OPD related to the affairs of education is still not effective, the Office of Education and Culture through its fields implements only normative but does not involve technically in the practical process in the field with the education sector of the Regional Development Planning Agency and the lack of intensive coordination and communication between the Agency Regional Development Planning with OPD located in the Office of Education and Culture.Keywords: Communication, Coordination, Education Sector.